Effects of Ellagic acid and Hesperetin on Levels of Some Elements in Livers of Aluminum-Induced Rats - Ozkaya, Ahmet; Ciftci, Harun; Dayangac, Alpaslan; Cevrimli, B. Sitki; Olcucu, Ali; Celik, Sait (Turkish Biochem Soc, 2013)
Objective: Ellagic acid and hesperetin are well known as having free radical scavenging activity in some rat tissues. Aluminum is known to cause toxic effects on various organ systems. In this study, the protective role of ellagic acid and hesperetin has been investigated on macro and trace elements in liver of rats treated with AlCl3. Method: Thirty-six healthy adult male Spraque-dawley rats (240+10 g body weight) were used in this study. The rats were randomly divided into six groups and Ellagic acid, Hesperetin, AlCl3, AlCl3+ Ellagic acid and AlCl3+Hesperetin were treated to each group except from the control group. Determinations of iron, calcium, copper and zinc were performed using a Flame Atomic Absorption Spectrometer and determination of aluminum and manganese were carried out with Inductively Coupled Plasma Atomic Emission Spectrometer. Results: Levels of aluminum, calcium and iron in AlCl3 treated group were found to be increased compared to the control group (p<0.01, p<0.001). In AlCl3+ Ellagic acid and AlCl3+Hesperetin treated groups, the levels of aluminum and calcium were found as decreased (p<0.05, p<0.001). When compared to the control group, level of manganese in liver were found to be increased in ellagic acid treated group (p<0.01). The zinc level of Hesperetin group increased when compared to the other groups (p<0.05). Conclusion: Our results suggest that ellagic acid and hesperetin may have a protective role upon major and trace elements against AlCl3-induced stress conditions.
Aluminyuma maruz kalmi{dotless}ş si{dotless}çanlari{dotless}n karaci?erlerindeki bazi{dotless} elementlerin seviyeleri üzerine hesperetin ve ellagik asitin etkileri
Keywords: Aluminum; Ellagic acid; Hesperetin; Trace elements; Calcium